Local application of adipose-derived mesenchymal stem cells supports the healing of fistula: prospective randomised study on rat model of fistulising Crohn's disease - Ryska, Ondrej; Serclova, Zuzana; Mestak, Ondrej; Matouskova, Eva; Vesely, Pavel; Mrazova, Iveta (Scandinavian journal of gastroenterology, 2017)
OBJECTIVE: Local application of adipose-derived mesenchymal stem cells (ADSC) represents a novel approach for the management of perianal fistula in patients with Crohn's disease. A randomised study on an animal model was performed to investigate the efficacy and to detect the distribution of implanted ADSCs by bioluminescence (BLI). MATERIALS AND METHODS: A caecostomy was used as a fistula model in 32 Lewis rats. The ADSCs were isolated from transgenic donor expressing firefly luciferase. Animals were randomly assigned to groups given injections of 4 × 106 cells (n = 16, group A) or placebo (n = 16, group B) in the perifistular tissue. Fistula drainage assessment was used to evaluate the fistula healing. After application of D-luciferin, cell viability and distribution was detected using an IVIS Lumina XR camera on days 0, 2, 7, 14 and 30. RESULTS: The fistula was identified as healed in 6 (38%) animals in group A vs. 1 case (6.3%) in group B (p = .033). The BLI was strongest immediately after administration of ADSCs 31.2 × 104 (6.09-111 × 104) p/s/cm2/sr. The fastest decrease was observed within the first 2 days when values fell by 50.2%. The BLI 30 days after injection was significantly higher in animals with healed fistulas - 8.23 × 104 (1.18-16.9 × 104) vs. 1.74 × 104 (0.156-6.88 × 104); p = .0393. CONCLUSIONS: Local application of ADSCs resulted in significantly higher fistula closure rate on an animal model. BLI monitoring was proved to be feasible and showed rapid reduction of the ADSC mass after application. More viable cells were detected in animals with healed fistula at the end of the follow-up.
Keywords: regenerativní lékařství; náhodné rozdělení; hojení ran; luminiscenční měření; tuková tkáň; Luminescent Measurements; Rectal Fistula; rektální píštěl; perianal fistula; Rats, Inbred Lew; Mesenchymal Stem Cell Transplantation; krysa rodu Rattus; výsledek terapie; Crohn Disease; zvířata; Wound Healing; Mesenchymal stem cell; transplantace mezenchymálních kmenových buněk; Male; mezenchymální kmenové buňky; bioluminescence; Treatment Outcome; Crohnova nemoc; potkani inbrední LEW; Rats; Animals; mužské pohlaví; prospektivní studie; Disease Models, Animal; Random Allocation; Regenerative Medicine; Adipose Tissue; Mesenchymal Stem Cells; modely nemocí na zvířatech; Prospective Studies